2008
DOI: 10.1016/j.neulet.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of androgen receptor expression in the ovine fetal central nervous system and pituitary

Abstract: In fetal sheep, circulating androgens influence fetal stress responsiveness and timing of parturition. Nevertheless, little is known about the presence and development of androgen receptors in the fetal brain. The present study was undertaken to test the hypothesis that expression of androgen receptor occurs in fetal brain and pituitary, and that the abundance of the AR is ontogenetically regulated. We isolated mRNA from pituitary, hypothalamus, hippocampus, and brainstem in fetal sheep that were 80, 100, 120,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The developmental time course of aromatase expression overlaps with the time when receptors for estrogens, androgens and progesterone are all present in the fetal sheep hypothalamus and AMYG (19,5557). The presence of estrogen receptors provides evidence that the molecular and cellular substrates for estrogen action are intact at midgestation in the fetal lamb and agree with physiological studies that suggest aromatization is involved in masculinization of sheep sexual behavior and suppression of the LH surge (28).…”
Section: Discussionmentioning
confidence: 94%
“…The developmental time course of aromatase expression overlaps with the time when receptors for estrogens, androgens and progesterone are all present in the fetal sheep hypothalamus and AMYG (19,5557). The presence of estrogen receptors provides evidence that the molecular and cellular substrates for estrogen action are intact at midgestation in the fetal lamb and agree with physiological studies that suggest aromatization is involved in masculinization of sheep sexual behavior and suppression of the LH surge (28).…”
Section: Discussionmentioning
confidence: 94%
“…Sexual maturation in mice occurs between 4 and 5 weeks in males and 2-3 weeks in females (Papaioannou et al 1989). It coincides with elevated levels of circulating steroid hormones, including glucocorticoids (Seckl 2004;Wood and Keller-Wood 2008). Our results suggest that sex difference in mRNA and protein expression levels of the PTHrP gene in adolescent mouse kidneys may be associated with sex-differences in circulating steroid levels.…”
Section: Discussionmentioning
confidence: 61%
“…GPR54 receptors are expressed in ruminant pituitary somatotropes (Smith et al 2008). E2 (Wood 2008), P4 (Ashley et al 2009) and T (Wood & Keller-Wood 2008) receptors are also located in the ruminant pituitary. The experimental protocol of the present study followed that of our previous study, which showed that E2 treatment (10 -8 mol/L) enhanced the GnRH-stimulated release of LH in bovine pituitary cells (Hashizume et al 2002).…”
Section: Discussionmentioning
confidence: 99%